Acute kidney injury rates during a single hospitalization undergoing tavr with or without pci in high-risk surgical candidates. a study using the national inpatient sample: 2011–2014. (25th November 2020) - Celli, D; Zarrabian, B; Byer, M; Munoz-Mendoza, J
Abstract: Introduction: Aortic valve stenosis (AS) and atherosclerosis share similar risk factors, therefore patients referred for replacement have incidental obstructive coronary lesions in 40–70% of the cases. Using the surgical approach of replacement, guidelines from observational studies give a class IIa recommendation for revascularization through CABG of major coronary arteries with >70% luminal stenosis or left main artery with >50% luminal stenosis at the time of valve replacement. In the event of high-risk surgical patients, TAVR is prompted and current recommendations support combined TAVR and percutaneous coronary intervention (PCI) for treatment of ostial/proximal lesions, or in unstable patients. Further characterization of complications is needed to allow experts to make a supported decision. Purpose: One of the biggest concerns when performing both procedures without a washing period is the increased renal burden. In the present study, we evaluated the outcomes and complications in patients undergoing TAVR and PCI during the same hospitalization. Methods: The patient population was obtained from the Nation Inpatient Sample database in the U.S. ICD-9 billing codes were used to identify all patients with severe AS undergoing PCI and TAVR during the same admission between 2011:2014. At this timeframe, only high-risk surgical patients were candidates for TAVR. Multivariate logistic regression was used to adjust for patient and procedural confounders. Results: Between 2011 and 2014, 31945 patients underwent TAVR out of which 1069 had a PCI during the same hospital admission. The adjusted odds ratio (OR) of an AKI was 2.44 (95% CI: 0.85–7.00) times greater in those who underwent a TAVR+PCI during the same admission compared to TAVR alone; however, this was not statistically significant (p=0.097). Mean length of stay was 10.6 days in the TAVR+PCI group, compared to 7.1 days in those who underwent a TAVR alone, p-value <0.05. In-hospital, all-cause mortality was 4.4 times greater in those receiving TAVR+PCI than TAVR alone (95% CI: 2.81–7.14). A multivariate regression model controlling for potential confounders was used to evaluate the likelihood of developing an AKI in the setting of CKD: the adjusted OR of stage I was 0.51 (95% CI: 0.09–2.92), stage II was 1.36 (95% CI: 0.52–3.51), stage III was 3.24 (95% CI: 1.10–9.58), stage IV was 0.96 (95% CI: 0.16–5.73), and stage V was 1.58 (95% CI: 0.59–4.24) when compared to normal renal function. Conclusion: Periprocedural PCI and TAVR during the same hospitalization have increased length of stay and in-hospital mortality compared to TAVR alone. However, the likelihood of an AKI in the setting of a concurrent PCI with TAVR was not statistically significant compared to a TAVR alone. Those with CKD Stage III were noted to have an increased likelihood of developing an AKI during their admission. This might give new insight for operators on the so feared contrast-associated nephropathy. Funding Acknowledgement: Type of funding source: None